(3MhGTi Ydi ZGjI GdeQGe ajeG jJYdb HCfcMI GdCfGes - (3CHh GdYHGS CMeO Hf YeQ GdOjQHis; (3CHh GdYHGS CMeO Hf YeQ GdOjQHjs
(3ChdgG (B:s
(3CeG HYO agPg MhGTi bO cfJ cJHJgG ai ChQGb hHghGeT cJGHfG GdeSei ZGjI GdeQGe ajeG jJYdb HCfcMI GdCfGe s
(3BNQgG (B:s
(3Ef de GdLhGH YfgG Ydi hLg MSf (B,(3GdMeO ddg GdgGOi Edi SHjd GdQTGO s
(3GdfSNI HgG MhGTs
(3ZGjI GdeQGe GfXQ EjVGM Gdecfhf L(B2 (3U` (B141s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdTGaYjs